2000
DOI: 10.1017/s0373463399008711
|View full text |Cite
|
Sign up to set email alerts
|

Human Factors Issues in Advanced Moving-map Systems

Abstract: Vector-based maps are an advanced capability of digital moving-map systems that are easily customised and can be powerful aids to aircrew information processing and decisionmaking. However, they may place excessive demands on an aircrew's information processing requirements, cause an increase in workload, and degrade situational awareness if the user interface is not designed properly. There is little information available about the human factors and situational awareness issues relevant to vector-based maps. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In recent years, studies involving subjective preference and objective performance have been carried out on different aspects and different types of software system, including websites [3] [4], moving-map systems [5], expert advisory systems [6], and graph layout algorithms [7]. A further paper by Purchase et al on variations of UML class diagrams [8] found that, where participants felt less at ease with a notation, they appeared to be more diligent in working with it, resulting in better performance.…”
Section: Links Between Preference and Performancementioning
confidence: 99%
“…In recent years, studies involving subjective preference and objective performance have been carried out on different aspects and different types of software system, including websites [3] [4], moving-map systems [5], expert advisory systems [6], and graph layout algorithms [7]. A further paper by Purchase et al on variations of UML class diagrams [8] found that, where participants felt less at ease with a notation, they appeared to be more diligent in working with it, resulting in better performance.…”
Section: Links Between Preference and Performancementioning
confidence: 99%
“…For example, websites [6], [7] moving map systems [8] and graph layout algorithms [9] have been studied in this context. The relationship between subjective preference and objective performance measures remains unclear after these studies, as the results have not been consistent.…”
Section: Preference and Performancementioning
confidence: 99%